2005
DOI: 10.2355/isijinternational.45.669
|View full text |Cite
|
Sign up to set email alerts
|

A Three-dimensional Mathematical Modelling of Drainage Behavior in Blast Furnace Hearth

Abstract: Stable blast furnace operation is required to reduce energy consumption in iron and steelmaking industry. For the stable blast furnace operation, precise controlled drainage is one of the important factors. However, the effects of the various in-furnace conditions on the stable operation were not examined well. Therefore, in this work, basic characteristic features of drainage in a blast furnace hearth were examined.Two-and three-dimensional mathematical model were developed based on the finite difference meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 8 publications
2
66
0
1
Order By: Relevance
“…An efficient and strictly controlled tapping is necessary for guaranteeing a stable operation and high productivity of the BF. Many recent investigations [1][2][3][4][5][6][7][8][9] on this subject have revealed that the pressure drop caused by fluid flow through the deadman in the hearth is a significant factor governing hearth drainage. However, due to the hostile environment, the possibilities to directly measure internal variables are practically nonexistent.…”
Section: Introductionmentioning
confidence: 99%
“…An efficient and strictly controlled tapping is necessary for guaranteeing a stable operation and high productivity of the BF. Many recent investigations [1][2][3][4][5][6][7][8][9] on this subject have revealed that the pressure drop caused by fluid flow through the deadman in the hearth is a significant factor governing hearth drainage. However, due to the hostile environment, the possibilities to directly measure internal variables are practically nonexistent.…”
Section: Introductionmentioning
confidence: 99%
“…38,134) Recently, attempts have also been made to model the gas-liquid-solid flow in BF hearth, where the effects of coke free zone, 85) natural convection and turbulent model 86,88) are investigated. Mathematical models have also been extended to identify the interface between slag and hot metal, 90) and establish the interrelationships between operation parameter, hearth condition and drainage behaviour. 91,92) The work described in this section may offer various methods to study the multiphase flow in a BF.…”
Section: Simulation Of the Multiphase Flowmentioning
confidence: 99%
“…Numerical predictions of liquid levels or liquid flow distributions in the hearth are usually based on the static equilibrium of forces acting on the submerged solid particles or an assumed position of deadman and porosity distribution in the submerged solid region. [83][84][85][86][87][88][89][90][91][92] The prediction of the deadman profile and its relation to solid or liquid flow pattern overcomes these deficiencies. Due to the discontinuous stress distribution between solid particles in the hearth, a continuum-based approach is difficult to apply.…”
mentioning
confidence: 99%
“…In a previous paper, 11) we developed a three-dimensional mathematical model, which can predict gas-slag and slag-iron interfaces shapes, total drainage rate, iron and slag drainage rates during a tap affected by various hearth conditions. The effect of various in-furnace conditions on drainage rates, gas-slag and slag-iron interfaces shapes and maximum gas-slag interfaces height were examined in another previous paper.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Many researchers attempted to solve the issues by using experimental and mathematical models. [1][2][3][4][5][6][7][8][9][10][11] However, there are many problems to understand drainage behavior in a blast furnace hearth because several important hearth values such as coke diameter, void fraction, temperature of iron and slag in the hearth, and levels of iron and slag cannot be measured during a tap. Because of these issues, there are many unrevealed phenomena in the blast furnace hearth.…”
Section: Introductionmentioning
confidence: 99%